Kriopreservasi Semen Kambing Peranakan Boer dengan Pengencer Andromed dan Ekstrak Daun Kelor - Riyadhi, Muhammad; Syarifuddin, Nursyam Andi; Sumantri, Ika; Wahdi, Anis; Rizal, Muhammad; Rizqiana, Sista; Bahtiyar, Saiul; Rifani, Muhammad Ade (IPB University, 2025)
The nutrients contained in Moringa leaves can protect spermatozoa from damage during semen cryopreservation. This study investigated the effectiveness of Moringa leaf extract in Andromed extender on the quality of frozen semen from Boer crossbreed goats. Fresh semen was divided into four tubes in equal volume and diluted with Andromed (control), 98% Andromed + 2% Moringa leaf extract (ME-2), 96% Andromed + 4% Moringa leaf extract (ME-4), and 94% Andromed + 6% Moringa leaf extract (ME-6), respectively. Diluted semen was placed in a mini-straw (0.25 mL), equilibrated in a refrigerator at 5°C for 4 hours, and then frozen by positioning the straw 10 cm above the surface of liquid nitrogen for 15 minutes. Variables were evaluated after diluting and thawing, including percentage of spermatozoa motility, live, and intact plasma membrane (IPM). Results of this study showed that the percentage of spermatozoa motility, live, and IPM for ME-4 (56.25, 67.5, and 65.75%) were significantly (p<0.05) higher than control (47.5, 56.75, and 53%), ME-2 (51.25, 59.5, and 56.25%), and ME-6 (51.25, 62.25, and 56%). This study’s findings indicate that adding 4% Moringa leaf extract to Andromed extender is optimal for enhancing the quality of frozen semen in Boer crossbreed goats.